Effectiveness of Proprioceptive Neuromuscular Facilitation on Walking Speed, Discomfort, and Knee Extension in an Acute Stroke Patient: A Case Study - Lee, Seunghak; Hong, Jiheon; Kim, Jinseop; Nam, Yeongyo; Yu, Jaeho (South Eastern European Journal of Public Health, 2024)
This study investigates the impact of proprioceptive neuromuscular facilitation (PNF) on improving functional mobility in a stroke patient, with a focus on walking speed, discomfort levels, and knee extension range of motion (ROM). PNF techniques were applied over four weeks to assess their effectiveness. The patient's walking performance was evaluated using the 6-minute walk test (6MWT), and discomfort was measured using the visual analogue scale (VAS) during walking and knee extension movements in both seated and standing positions. The results revealed a significant reduction in 6MWT time from 16.47 seconds to 14.2 seconds post-intervention. VAS scores showed a marked decrease in discomfort during the 6MWT from 8 to 1 and during knee extension from 7 to 4 in both positions. Additionally, the knee extension ROM increased significantly, with the most pronounced improvement observed in the seated position (from 141.3° to 158.5°). These findings suggest that PNF is an effective therapeutic approach for enhancing walking performance and reducing discomfort related to hamstring stiffness in acute stroke patients. The study's limitations include its single-case design, limiting the generalizability of the results. Future research with a larger sample size and more objective assessment tools is recommended to validate these findings.